2019
DOI: 10.1021/acsami.9b15073
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Structural Evolution and Lattice Water Movement for Rhombohedral Nickel Hexacyanoferrate upon Sodium Migration

Abstract: Prussian blue analogues (PBAs) have been regarded as prospective cathode materials for sodium-ion batteries due to tunable chemical composition and structure. Herein, a high-performance rhombohedral nickel hexacyanoferrate is synthesized via a controllable low-temperature reaction process. It can deliver impressive capacity retention of 87.8% after 10 000 cycles at 10C and high rate discharge capacity of 53 mAh g–1 at 40C. According to the structural evolution and lattice water movement, superior electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…Besides, the abundance of 24d sites in the PBA framework (20 24d sites) also guarantees the enhanced Na+ diffusion in PBA frameworks. This nonlinear Na + diffusion mechanism was further confirmed by Zuo's group, [ 68 ] especially when there exists interstitial water in the body‐center position of the framework. To promote the diffusion kinetics in PBA materials, it is useful to employ strategies including the reduction of crystal water and metal doping control, which will be discussed in the later part.…”
Section: Electrode Reaction Mechanismssupporting
confidence: 53%
See 2 more Smart Citations
“…Besides, the abundance of 24d sites in the PBA framework (20 24d sites) also guarantees the enhanced Na+ diffusion in PBA frameworks. This nonlinear Na + diffusion mechanism was further confirmed by Zuo's group, [ 68 ] especially when there exists interstitial water in the body‐center position of the framework. To promote the diffusion kinetics in PBA materials, it is useful to employ strategies including the reduction of crystal water and metal doping control, which will be discussed in the later part.…”
Section: Electrode Reaction Mechanismssupporting
confidence: 53%
“…Xie et al. [ 68 ] revealed that Ni 2+ in NiHCF can effectively reinforce the lattice framework by alleviating the alterations of cell volume and stress−strain caused by Na + ion migration and structure transition. Furthermore, Lee et al.…”
Section: Electrode Reaction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of other PBA modifications confirmed that the cubic phase has superior cycling stability relative to the distorted versions [142,146] . However, a study of rhombohedral Na 1.34 Ni[Fe(CN) 6 ] 0.81 showed that the material goes through a highly reversible two‐phase reaction from rhombohedral at low voltages to cubic at high voltages, which also gives great cycling stability [144] . Na x FeFe(CN) 6 and Na x FeCo(CN) 6 were also studied with operando XRD showing only minor structural changes during cycling [145,147] …”
Section: X‐ray Diffraction and Scatteringmentioning
confidence: 99%
“…[23] However, upon electrochemical lithiation in organic electrolyte, the relatively minute water content will not hinder insertion of Li + ions. Before electrochemical lithiation, the samples were dried under vacuum at 60 °C for a minimum of 6 h to remove any adsorbed moisture, as presence of moisture can lead to structural instabilities, side reactions, and electrochemical property change in PBA analogues [24][25][26] during high voltage operation. The structure of LiFePBA is illustrated in Figure 1a, consisting of a 3D network of Fe 1 CNFe 2 chains along the edges of the unit cell cube.…”
Section: Conformal Deposition Of Pba On Highly Porous Current Collectorsmentioning
confidence: 99%